Inhibiting in situ phase transition in Ruddlesden-Popper perovskite via tailoring bond hybridization and its application in oxygen permeation - Han, N.; Guo, X.; Cheng, J.; Liu, P.; Zhang, S.; Huang, S.; Rowles, Matthew; Fransaer, J.; Liu, Shaomin (ELSEVIER, 2021)
Ruddlesden-Popper perovskite oxide (An+1BnO3n+1) mixed ionic-electronic conducting membranes are proposed as a new method for oxygen separation from air. Element doping was used to improve the ionic conductivity and to stabilize the crystal structure. The doping of orthorhombic Pr2NiO4 with Mo resulted in the ex situ collapse of the crystal together with the generation of impurities by the rearrangement of Pr atoms. Mo doping also inhibited the in situ phase transition from low-order Pr2NiO4 to high-order Pr4Ni3O10 by weakening the covalent interaction between Pr and O. Membranes made from Pr2Ni0.95Mo0.05O4+δ showed an oxygen flux of 3.35 mL min−1 cm−2 at 1,000°C, high permeation stability in air and helium, and high CO2 tolerance with no decline of oxygen flux during 500 h at 900°C. This work advances a comprehensive understanding of phase transitions on Pr2Ni1−xMoxO4 and provides an effective way to improve the oxygen permeability via in situ stabilization of the phase structure.